River chief governance in China: trends and outlooks - Yang, Chenxinyi; Song, Tao (Frontiers in Environmental Science, 2024)
The issue of water resources is a perennial topic for achieving human sustainable development goals. Over the last decade, a renewed watershed governance regime, River Chief System emerged to solve the issue of river pollutions in China, and attracted attentions across the world. In this review article, we profiled River Chief System, including its origin, principle and characteristics, and found that the primary feature of River Chief System is its hierarchical structure and the implementation of responsibility.By triangulating bibliometric measurement of the Citespace tool, database of the Web of Science and the China National Knowledge Infrastructure, the development, research trends and hotspots of River Chief System research have been reviewed systematically.The number of publications of River Chief System is showing a significant growing trend, and their foci are diverse: water environmental effects, mechanisms of River Chief System, public participation and supervision and localization of River Chief System, and the implement of "One River, One Policy" plan. Finally, theoretical and practical suggestions for the future study of River Chief System are proposed. This review systematically introduces China's experience on river management to the world, which is of great significance for the world to fully understand the River Chief System of China and further improve and promote it.